The Influence Of Corporate Social Responsibility On Customer Loyalty Through Trust And Electronic Word Of Mouth At Emina Cosmetics - Keisha Attila Fardhana; Gracia Ongkowijoyo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study was conducted to analyze the influence of Corporate Social Responsibility (CSR) on customer loyalty through trust and Electronic Word of Mouth (E-WOM) in Emina Cosmetics consumers. This research was carried out with a quantitative method through the distribution of questionnaires to Emina Cosmetics consumers who have purchased Emina products. This study utilizes data sourced from questionnaires that have been filled out by Emina Cosmetics consumers who have purchased products, with 160 respondents' data processed using the PLS-SEM method assisted by SmartPLS 4. This research shows that CSR has been proven to be able to increase consumer trust, E-WOM, and customer loyalty. In addition, trust and E-WOM have also proven to be bridges that connect CSR with customer loyalty, where E-WOM has a much stronger role than trust. These findings confirm that relevant and efficiently communicated CSR programs through digital media can encourage consumers to share positive experiences, ultimately strengthening customer loyalty in a sustainable manner.